PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (STUDI KASUS DI SMP PLUS FITYAANI KARANGPLOSO KABUPATEN MALANG) - Indriani Rachman Saputri; Lia Nur Atiqoh Bela Dina; Dzulfikar Rodafi (VICRATINA, 2022)
This research was motivated by the imbalance interactions between student and teacher in learning activities. Because of that the teachers at SMP Plus Fityaani decided to apply the group investigation learning model. The purpose of this study is to describe how the planning, implementation process, and the results of the group investigation learning model in PAI lessons at SMP Plus Fityaani Karangploso. This research uses a qualitative approach with a descriptive case study type. Data collection procedures were carried out using observation, interviews and documentation techniques. Sources of data are taken from primary data and secondary data. The data analysis techniques in this study include data collection, data reduction, data presentation, and drawing conclusions. While checking the validity of the data using attendance extension, triangulation, and peer discussion. Based on the results of the research, it is known that in the process of planning the group investigation model, the things teachers do are making lesson plans, making learning media and preparing learning topic materials. At the implementation stage, a series of activities carried out are opening activities, core activities and closing activities. While the results obtained after the implementation of the group investigation model are that students are more active in learning, increase student understanding, increase student confidence and grow the spirit of social cooperation between students